Factores que limitan la implementación del planeamiento tributario en empresas de la ciudad de Iquitos año 2023 - Huapaya Isuiza, Andrea Lucia (2024)
In the business world, implementing strategies that allow an improvement in the organization is relevant because this is reflected in its performance and daily operations, thus, tax planning is considered an effective tool that when implemented brings with it benefits such as tax savings, lower risk of tax infractions, regulatory compliance, among others. The aim of this study was to determine which are the factors that limite the implementation of tax planning in companies in the city of Iquitos, for this the participation of 60 representatives of companies dedicated to the commercial sector was taken into account, this research was carried out with a quantitative approach, according to its scope it was observational and had a non-experimental design, also the survey technique was used, the instrument of collection of the questionnaire, which contained 24 key questions that, due to the nature of their answers, are considered on a Likert scale from strongly agree to strongly disagree. Given the analysis of the results, it was significantly determined that economic factors are present when these are more than two factors, in the same way cultural factors are present because these are more than two and political-business factors are present because it is reflected in the fact that there are more than two.